2020
DOI: 10.1111/faf.12517
|View full text |Cite
|
Sign up to set email alerts
|

Seabird‐induced natural mortality of forage fish varies with fish abundance: Evidence from five ecosystems

Abstract: Forage fish populations often undergo large and rapid fluctuations in abundance. However, most of their predators are buffered against such fluctuations owing to their slower pace of life, which allows them to maintain more stable populations, at least during short periods of food scarcity. In this study, we investigated top-down processes exerted by seabirds on forage fish stocks in five contrasted marine ecosystems, compiling numerous datasets on seabird counts, diets, energetic needs and prey energy content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 119 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…The relative proportion of a fish species represented in the predator diet is commonly used and has been correlated with abundance of age‐0 fish in local environments (e.g., Mills et al, 2007; Piatt et al, 2018), but this relationship varies with degree of diet specialization and spatio‐temporal overlap between predator and prey. Recognizing the potential significance of sampling of age‐0 fish early on, Cairns (1992) suggested in a unique paper that several seabird‐based dietary parameters could be used as leading indicators of potential recruitment and year class strength, as well as direct inputs needed for models of variable natural mortality (e.g., Hill et al, 2020; Saraux et al, 2021). Notably, Cairns assumed that relationships between seabird diet and year class strength would be non‐linear.…”
Section: Introductionmentioning
confidence: 99%
“…The relative proportion of a fish species represented in the predator diet is commonly used and has been correlated with abundance of age‐0 fish in local environments (e.g., Mills et al, 2007; Piatt et al, 2018), but this relationship varies with degree of diet specialization and spatio‐temporal overlap between predator and prey. Recognizing the potential significance of sampling of age‐0 fish early on, Cairns (1992) suggested in a unique paper that several seabird‐based dietary parameters could be used as leading indicators of potential recruitment and year class strength, as well as direct inputs needed for models of variable natural mortality (e.g., Hill et al, 2020; Saraux et al, 2021). Notably, Cairns assumed that relationships between seabird diet and year class strength would be non‐linear.…”
Section: Introductionmentioning
confidence: 99%
“…Homing in on seabirds, a global comparative study based on observational data showed a significant decline in the breeding success of seabirds across multiple marine ecosystems when their prey bases dropped to below one third of maximum abundance levels (Cury et al, 2011). Furthermore, a recent study drawing on data from the same ecosystems suggests that forage fish should be carefully managed so as to remain at levels above 18% of maximum abundance levels, since predation mortality inflicted on forage fish by seabird predators significantly increases below this fish abundance level (Saraux et al, 2020). The need for conservative management measures at low stock levels may be even more crucial as we suffer the effects of climate change.…”
Section: A Brief Overview Of the Role Of Small Pelagic Fish In Marine Ecosystemsmentioning
confidence: 99%
“…Several marine species inhabiting South African waters, and relying on forage fish as prey, are either charismatic and important for ecotourism, commercially valuable and/or are species of conservation concern, including three endemic species of endangered seabirds (African penguin Spheniscus demersus, Cape gannet Morus capensis, and Cape Cormorant Phalacrocorax capensis), great white shark Carcharodon carcharias, Bryde's whale Balaenoptera edeni, common dolphin Delphinus delphis, dusky dolphin Lagenorhynchus obscurus, and Cape fur seal Arctocephalus pusillus. Sardine Sardinops sagax and anchovy Engraulis encrasicolus comprise notable portions of the diet of many top predators off South Africa: African penguin -79%, Cape gannet -58%, Cape Cormorant -98%, and snoek Thyrsites atun -46%, Cape hake Merluccius capensis and M. paradoxus -10 to 40% depending on hake size class considered, yellowtail Seriola lalandei -30%, geelbek Atractoscion aequidens -20%, Bryde's Whale -82%, cetaceans in general -37%, and Cape fur seal -30% (Saraux et al, 2020). Economically valuable predatory fish include geelbek and yellowtail, both especially caught in the line fishery, and both heavily dependent on availability of anchovy and sardine prey.…”
Section: A Brief Overview Of the Role Of Small Pelagic Fish In Marine Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seabirds are important indicator species for changes in fish stock composition, and thus the status of the marine food web and ecosystem as a whole (Furness & Camphuysen 1997, HELCOM 2018. As seabirds compete with forage fisheries for prey, estimating their prey requirements is essential for achieving good conservation status (Sydeman et al 2017, Saraux et al 2020, Hentati-Sundberg et al 2021. Diet and prey choice are key parameters for estimating prey consumption and prey requirements, and good estimations of these parameters are necessary for evaluating potential overlap between fisheries and marine top predators (Hansson et al 2018).…”
Section: Introductionmentioning
confidence: 99%